INFORMATION AND COMMUNICATION TECHNOLOGY IN THE CONTEXT OF MODERN INTERNATIONAL RELATIONS: SOCIAL AND PHILOSOPHICAL ANALYSIS - Пода, Т. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2014)
The article analyzes the modern information and communication technologies and their impact on the system of international relationsand state`s foreign policy and nongovernmental actors.